The Olympic Idea and the principle of fair play in activities of polish sports associatins in the city of Lodz in the period of The Second Republic - Kędzia, Piotr (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
The goal of this article is portraying the aspects associated with the Olympic Idea and the principle of fair play in activities of Polish sports associations in the city of Lodz in the interwar period. In the paper were presented genesis of Olympism and sports clubs and contexts of multidirectional action for popularizing Olympic values. Quoted examples from the life of Polish sports associations constitute still a little unfamiliar area the sports activity and culture the city of Lodz.